1977
DOI: 10.1111/j.1751-0813.1977.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diarrhoea, Tail Length and Sex on the Incidence of Breech Strike in Modified Mulesed Merino Sheep

Abstract: Merino sheep were treated with purgative to induce scouring and the effects of tail length and sex on the incidence and origin of breech strike were examined. In sheep treated with the modified Mules operation, those with tails docked very short were strongly predisposed to tail strike, and to a lesser extent, crutch strike. Tails docked level with, or just below, the tip of the vulva in ewes, and at the equivalent length in wethers, were struck far less frequently. Within each tail length group, wethers tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…In Western Australia over one season 1.9% of radically mulesed sheep were struck on the breech compared to 6.7% of un‐mulesed sheep 7 . Good technique also involves docking tails to the level of the base of the vulva and retaining some wool bearing skin on the tail to minimise cancer 1,8, 9…”
mentioning
confidence: 99%
“…In Western Australia over one season 1.9% of radically mulesed sheep were struck on the breech compared to 6.7% of un‐mulesed sheep 7 . Good technique also involves docking tails to the level of the base of the vulva and retaining some wool bearing skin on the tail to minimise cancer 1,8, 9…”
mentioning
confidence: 99%
“…18 Despite dag becoming an increasingly important risk factor for breech-strike, and urine stain less so, high stain score was occasionally identified as a risk factor in the clipped and unmulesed ewes in the current study. 18 Despite dag becoming an increasingly important risk factor for breech-strike, and urine stain less so, high stain score was occasionally identified as a risk factor in the clipped and unmulesed ewes in the current study.…”
Section: Odds Ratios and 95% Confidence Interval (Ci) Of Risk Factorsmentioning
confidence: 52%
“…However, scientific studies are not unanimous: whereas French et al (1994a) showed that intact lambs underwent more fly attacks than docked lambs, in relation with improved rear cleanliness, two other studies (French et al, 1994b;Snoep et al, 2002) showed that docking was associated neither to a lower myiasis prevalence nor to less insect attacks. In addition, docking lambs too short can increase the incidence of fly strike (Watts and Marchant, 1977;Watts and Luff, 1978; see also Watts and Perry, 1975;. Furthermore, in spite of their results, French et al (1994a) concluded that more adequate control of diarrhoea and development of reliable alternative methods of blowfly strike management should be considered, because of the dichotomy between the proportion of docked lambs (about 100%) and the relatively low proportion of lambs likely to be struck (125 attacks for 3172 studied lambs).…”
Section: Lefebvre Lips ö Dberg and Giffroymentioning
confidence: 99%